Impact of psoriasis severity on patient-reported clinical symptoms, health-related quality of life and work productivity among US patients: real-world data from the Corrona Psoriasis Registry. Issue 4 (20th April 2019) - Strober, Bruce; Greenberg, Jeffrey D; Karki, Chitra; Mason, Marc; Guo, Ning; Hur, Peter; Zhao, Yang; Herrera, Vivian; Lin, Feng; Lebwohl, Mark
Abstract : Objectives: This analysis examined the association between psoriasis severity, assessed by body surface area (BSA) and the Investigator's Global Assessment (IGA; previously used only in clinical trials), and patient-reported outcomes (PROs) in a real-world setting. Design: Cross-sectional analysis within the Corrona Psoriasis Registry, an independent, prospective registry. Setting: 70 dermatology practices in the USA. Participants: 1529 adult patients with psoriasis being treated with biological or non-biological systemic psoriasis treatment by 31 May 2016. Primary and secondary outcome measures: Psoriasis severity was assessed by percentage of affected BSA (mild (0%–5%), moderate (>5%–10%), severe (>10%–15%), very severe (>15%)) and IGA scores (clear/almost clear (0–1), mild (2), moderate (3), severe (4)). PROs (pain, itch, fatigue; Dermatology Life Quality Index [DLQI]; EuroQoL Visual Analogue Scale [EQ-VAS]; Work Productivity and Activity Impairment [WPAI]) were compared across BSA and IGA levels using analysis of variance and X 2 tests. The association between psoriasis severity and PROs was examined using multivariable regression models. Results: The mean age was 50.6 years and 47% of patients were female. Consistently with more severe psoriasis, symptoms worsened, DLQI scores increased (p<0.05 for each level of BSA and IGA), EQ-VAS decreased (p<0.05 for each level of BSA and IGA) and WPAI scores increased. By BSA score, moderate to very severe psoriasis was associated with poorer outcomes for the 'impairment while working' and 'daily activities impaired' WPAI domains (all p<0.05 vs mild psoriasis). Very severe psoriasis was associated with increased 'work hours missed' and 'work hours affected' (both p<0.05 vs mild psoriasis) Findings were similar by IGA. Results were confirmed by multivariable regression analyses. Conclusions: In a real-world setting, more severe psoriasis, assessed by BSA and IGA, was consistently associated with worse PROs.